Relevance of the development of wine tourism in Uzbekistan - Rakhimov Abror (International Journal on Orange Technologies, 2021)
This article describes the current situation of world tourism market and its contribution to the world economy. Moreover, article highlights the concept of business tourism and its essential branch WINE tourism, the development of WINE tourism in regions, its significance and importance to develop in our country.